2022
DOI: 10.3390/vaccines10020198
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Validation of the Roche Elecsys SARS-CoV-2 Antigen Electro-Chemiluminescent Immunoassay in a Southeast Asian Region

Abstract: Introduction: SARS-CoV-2 antigen tests can complement and substitute for RT-PCR tests. Centralized laboratory automated SARS-CoV-2 antigen tests that can be scaled to process a large number COVID-19 cases simultaneously are now available. We have evaluated the new Roche Elecsys SARS-CoV-2 antigen electro-chemiluminescent immunoassay. Methods: The Roche SARS-CoV-2 antigen assay is a double-antibody sandwich electro-chemiluminescent immunoassay, which reports a cut-off index (COI) (COI ≥ 1.0 considered positive)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Three of the four AATs had similar analytical and clinical sensitivities, whereas the Liaison AAT from Diasorin had a significantly lower analytical and clinical sensitivity. This was unexpected, as previous studies evaluating each of the AATs have shown similar sensitivities [ 8 , 9 , 10 , 11 , 12 ]. Our findings highlight the need for comparison studies to allow direct comparison of different diagnostic tests.…”
Section: Discussionmentioning
confidence: 78%
“…Three of the four AATs had similar analytical and clinical sensitivities, whereas the Liaison AAT from Diasorin had a significantly lower analytical and clinical sensitivity. This was unexpected, as previous studies evaluating each of the AATs have shown similar sensitivities [ 8 , 9 , 10 , 11 , 12 ]. Our findings highlight the need for comparison studies to allow direct comparison of different diagnostic tests.…”
Section: Discussionmentioning
confidence: 78%
“…If the COI value of the test sample is more than 1, it is considered positive; otherwise it is negative. 50 As shown in Fig. 7(a), the signal intensity of the test line was correlated with the COVID-19 virus N protein content of the sample.…”
Section: Resultsmentioning
confidence: 84%
“…If the COI value of the test sample is more than 1, it is considered positive; otherwise it is negative. 50 As shown in Fig. 7 S1, † the test values of each sample uctuated slightly around the average, and the coefficient of variations (CVs) were within 10%.…”
Section: Analytical Methods Papermentioning
confidence: 75%
“… 39 Using RT-PCR as a reference, the sensitivity was over 90% at Ct ≤ 30, and the sensitivity of the assay was higher within the first week of onset than after 1 week. 40 …”
Section: Radmentioning
confidence: 99%